Human Health Risk Assessment of Heavy Metals in the Serayu River Water, Central Java-Indonesia - Handayani, Cicik Oktasari; Zu'amah, Hidayatuz; Sukarjo (Universitas Airlangga, 2025)
Introduction: Pollution is a major factor contributing to the decline in river water quality, which serves as a source of clean water for residents. This study examines the pollution degrees of heavy metals, including lead, cadmium, chromium, nickel, arsenic, cobalt, and manganese, in surface water, as well as the associated public health risks for adults and children. Methods: Water samples were obtained from 18 unique sites along the Serayu River in Central Java Province. The concentrations of heavy metals were measured utilizing an Atomic Absorption Spectrophotometer. The heavy metal pollution index was employed to evaluate the Serayu River's suitability as drinking water. Public health risks were evaluated by employing the hazard quotient (HQ), hazard index (HI), and carcinogenic risk estimation. Results and Discussion: The heavy metal pollution index exceeded 100 at several sampling sites (W1, W2, W3, W4, W6, W7), indicating that the water is unsafe for drinking. However, non-carcinogenic risks from metal ingestion are negligible, as the HI and HQ values for both adults and children remain below one. The estimated carcinogenic risk is within the acceptable threshold (1E-4), with values of 1.109E-6 for adults and 4.199E-6 for children, suggesting no significant carcinogenic risk to the population. Conclusion: The results indicate that the Serayu River does not pose a significant carcinogenic or non-carcinogenic for illness to adults and children. However, owing to their heightened susceptibility to toxic effects, monitoring strategies to address the elevated vulnerability of children to heavy metal exposure